التحليل الإيديولوجي والمنهجي عن الحفريات الإسرائيلية في القدس والمسجد الأقصى المبارك: Ideological and Methodological Analysis on Israeli Excavations in Islamicjerusalem and al-Aqsa Mosque - Amro, Arafat Mohammad; Yatiban, Aminurraasyid (Journal of Al-Tamaddun, 2024)
This study aims to analyse alternative cultural awareness among nations, understanding the intellectual invasion strategies and accompanying colonial normalization policies. This research employed a critical and analytical approach, comparing information gathered from previous literature, institutional documents, Jerusalem archaeological institutes, and daily observations stemming from a long-standing work in the city. It utilized scientific and unbiased analytical methods, particularly in conflict settings, drawing on the settler colonial theory and the Copenhagen School of Security Studies. The study found that these excavations, from their inception, have been ideologically driven with a biblical settler agenda as their primary methodology in dealing with archaeological evidence and Arab historical records on this land. The main objective is to entrench biblical narratives as historical realities, even though falsification and distortion, including erasing and Judaizing all evidence contradicting Jewish beliefs. This serves the broader aim of entrenching the colonial Zionist entity in Palestine and fulfilling the so-called biblical concept of "Greater Israel" in the heart of the Arab world.